Comparison of outcomes for balloon dilation of the Eustachian tube under local vs general anesthesia - Toivonen Joonas; Dean Marc; Kawai Kosuke; Poe Dennis (WILEY, 2022)
Objective
To compare the effectiveness of balloon dilation of the Eustachian tube (BDET) under local versus general anesthesia in the treatment of obstructive Eustachian tube dysfunction (OETD).
Study Design Retrospective review.
Methods Consecutive patients ages >= 18 with persistent OETD having failed adequate medical therapy underwent BDET between 2013 and 2018 under local or general anesthesia. Inclusion criteria were persistent type B or C tympanograms with symptoms or type A with symptoms upon barochallenge. Objective outcome measures were tympanometry, otoscopy and the need for additional subsequent intervention (revision dilation and tympanostomy tube). Primary outcome (failure) was defined as no change or worse in tympanogram.
Results The 191 patients (332 ETs), ages 18-88 years (mean 58.0) underwent BDET. The 112 patients (59%) were female. The 107 procedures (32%) were performed under local anesthesia. Mean duration of follow-up was 3.1 years (SD 1.9). Tympanograms improved to type A in 88% for BDET under local and 74% for general anesthesia at 12 months. Probability of being failure-free at 5 years was 70% (95% confidence interval [CI]: 52%-82%) in the local anesthesia group versus 65% (95% CI: 55%-73%) in the general anesthesia group. Risk of failure did not significantly differ between the groups (HR = 0.60; 95% CI: 0.27-1.31; p = .20).
Conclusion BDET under local anesthesia is effective in treating OETD and results in sustained improvements over 2 years. The procedure was successfully performed in all but one case utilizing a precise anesthesia protocol, and results are comparable with the procedure performed under general anesthesia. Level of evidence 4